Isolation and identification, genome-wide analysis and pathogenicity study of a novel PRRSV-1 in southern China - Xu, Huirui; Xie, Yongsheng; Deng, Kehui; He, Dongsheng (Frontiers in Microbiology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) has caused severe economic losses to the global swine industry. In recent years, the incidence of PRRSV-1 has been gradually increasing in China, but there are still few studies on it. In this study, clinical samples for PRRS virus isolation were collected from a pig farm in South China in 2022. We effectively isolated a strain of PRRSV utilizing PAM cells and demonstrated its consistent transmission capability on Marc-145 cells. The isolated strain was confirmed as PRRSV-1 by RT-qPCR, IFA, electron microscopy, etiolated spot purification and whole genome sequencing, the strain was named GD2022. The length of GD2022 genome is 15058nt; Based on the genome-wide genetic evolutionary analysis of GD2022, the strain was classified as PRRSV-1. Further genetic evolutionary analysis of its ORF5 gene showed that GD2022 belonged to PRRSV-1 subtype 1 and formed an independent branch in the evolutionary tree. Compared with the sequence of the classical PRRSV-1 strain (LV strain), GD2022 has several amino acid site mutations in the antigenic region from GP3 to GP5, these mutations are different from those of other PRRSV-1 strains in China. Recombination analysis showed no recombination events with GD2022. In addition, piglets infected with GD2022 displayed clinical respiratory symptoms and typical pathological changes.In this study, a strain of the PRRSV-1 virus was isolated using both PAM cells and Marc-145 and proved to be pathogenic to piglets, providing an important reference for the identification, prevention, and control of PRRSV-1.